Genome-wide analysis of DNA methylation and their associations with long noncoding RNA/mRNA expression in non-small-cell lung cancer. (February 2017) - Feng, Nannan; Wang, Yu; Zheng, Min; Yu, Xiao; Lin, Hongyan; Ma, Rong-Na; Shi, Oumin; Zheng, Xiangqian; Gao, Ming; Yu, Herbert; Garmire, Lana; Qian, Biyun
Aim: The goal of this study is to identify differentially methylated (DM) loci associated with long noncoding RNA (lncRNA)/mRNA expression in non-small-cell lung cancer (NSCLC).Materials & methods: Microarrays were used to interrogate genome-wide methylation and expression of lncRNA/mRNA in NSCLC.Results: We identified 113, 644 DM loci between tumors and adjacent tissues. Among them, 26, 310 DM loci were associated with 1685 differentially expressed genes, and 839 genes had significant correlations between methylation and expression, of which 26 hypermethylated loci in transcription start site 200 were correlated with low gene expression. We validated the correlations between methylation and expression in five genes ( CDO1, C2orf40, SCARF1, ZFP106 and IFFO1 ) using pyrosequencing and quantitative polymerase chain reaction. We also found significant correlations between lncRNAs and mRNAs, and validated four of the correlations with quantitative polymerase chain reaction.Conclusion: Integrated analysis of genome-wide DNA methylation and lncRNA/mRNA expression allows us to identify new DM loci -correlated with gene expression in NSCLC.